(untitled) (Il Politico, 2023)
Paolo Buzzi was one of the most representative exponents of the first generation of literary Futurism. He was a poet, novelist and playwright, engaged in the avant-garde battles of the early 20th century. He also worked at the Province of Milan for almost forty years (1898-1935), eventually holding the position of General Secretary. This paper analyses the early years of Buzzi’s bureaucratic career: a man of letters as a vocation, forced by necessity into a job in the local civil service. In addition to the unpublished and printed provincial archival documentation, Buzzi’s private archive, kept at the Central Municipal Library in Milan, was consulted. Among his papers is the ponderous, never published, five-volume autobiography entitled Bread and Poetry, which contains brief, fragmentary references to his bureaucratic work. Thus, a representation from within the public service emerges.